An electrochemical study of hydrogen in molten 2LiF-BeF2 (FLiBe) with addition of LiH. (20th January 2021) - Carotti, Francesco; Liu, Ertai; Macdonald, Digby D.; Scarlat, Raluca O.
Abstract: The chemical and transport behavior of hydrogen isotopes in molten 2LiF-BeF2 (FLiBe) is of interest for the design of tritium management systems in nuclear fission and fusion reactors that use FLiBe. The chemical reaction of LiH with FLiBe is used to introduce hydrogen in the molten salt and electrochemical methods are used for in situ studies of hydrogen in FLiBe. LiH reacts with molten FLiBe to generate an electroactive species whose voltammetry peak is proportional to the added quantity of LiH. The cyclic voltammetry reaction potential of 2.009 ± 0.050 V v s Be / Be 2 + and the electron exchange of n = 0.8 ± 0.5 are consistent with the one-electron oxidation of dissolved H in the zero valence state, H o to H + . The concentration of H o is estimated by linear sweep voltammetry at 60–80% of the hydrogen introduced by the reaction of 0.42 mol% LiH with FLiBe and after eleven hours it remains above 40%. It is postulated that covalent BeH2 is formed in FLiBe upon LiH addition, as a FLiBe-soluble quasi-stable intermediate product. The results provide an evaluation of LiH as a means of introducing dissolved hydrogen in FLiBe, enabling electrochemical methods as tools to advance the understanding of the chemistry of hydrogen isotopes in FLiBe.